Outcomes of Open Knee Joint Injuries in Trauma Patients at Tibebe-Ghion Specialized Hospital, Bahir-Dar, Ethiopia - Getachew Wuhib Shumye; Melatwork Assefa Wolle; Mekuriaw Wuhib Shumye; Leul Mekonnen Zeru (Emergency Care and Medicine)
Background: Open knee joint injury is a deep traumatic laceration violating the joint capsule. This study aimed to assess outcomes and associated factors of open knee joint injuries in trauma patients at Tibebe-Ghion Specialized Hospital, Bahirdar, Ethiopia, 2021. Methods: An institution-based retrospective cross-sectional study was conducted by reviewing the medical records of 43 patients treated for open knee joint injuries from January 2019 to July 2021, with an 86% response rate. Data were entered and exported using Epidata Manager Version 4.4 and analyzed using SPSS version 25. Results: Fourteen (32.5%) of the study subjects developed either infections or limping during follow-up due to open knee injuries, with the majority of injuries (58.1%) being caused by car accidents. The presence of associated injuries, wound size, time to wound closure, debridement as a management option, sex, and diagnostic methods showed a significant association with complication outcomes. Among the diagnosed infections, 90% were cases of septic arthritis. During the study period, eight patients (18.6%) developed limping during follow-up. The complication rate among open knee injury patients in the study area was significantly high, with one-third of patients experiencing complications. Targeted public awareness campaigns like car accidents should be conducted to educate the population about orthopedic emergencies and strategies to reduce complication risks, aiming for more favorable outcomes.